The Dali model in risk-management practice: The case of financial services firms - Rebecca Dalli Gonzi; Simon Grima; Murat Kizilkaya; Jonathan Spiteri (Journal of Risk and Financial Management, 2019)
Originality/value-this model contributed to the vast literature on models of change and risk management within organisations, but was not validated empirically for reliability of the factors, and on financial services providers within small jurisdictions. Therefore, the significance and importance of such a study lies firstly on the premise that testing on small countries can be deemed as small laboratories for more complex politics, regulations and policies of larger countries and secondly, the importance of financial services as essential for prosperity in a country's economy. This model will provide an empirically tested proactive model in a specific environment for managing organisational risks to arrive at their objectives with minimal setbacks.
Keywords: 330; change management; decision-making model; good governance; process improvement; resource management; risk management